Natural Variability Has Concealed Increases in Western US Flood Hazard Since the 1970s. Issue 7 (5th April 2022) - Bass, Benjamin; Norris, Jesse; Thackeray, Chad; Hall, Alex
Abstract: Flood hazard across the western United States (US) has generally shown decreasing trends in recent decades. This region's extreme streamflow is highly influenced by natural variability, which could either mask or amplify anthropogenic streamflow trends. In this study, we utilize a technique known as dynamical adjustment to assess historical (1970–2020) annual maximum 1‐day streamflow (Qx1d) from unregulated basins across the western US with and without the impact of natural variability. After removing natural variability, the fraction of basins with a positive (>5%) trend in Qx1d shifts from 25% to 53%. Basins with increasing (decreasing) Qx1d trends after dynamical adjustment exhibit weak (strong) drying, and furthermore are associated with intensifying precipitation extremes and/or large decreases in snowpack. Increasing flood hazard will likely emerge for such basins as the current phase of natural decadal variability shifts, and anthropogenic signals continue to intensify. Plain Language Summary: Historical observations of streamflow provide important insight into how the water cycle is responding to a changing climate. In particular, changes to extreme streamflow values, associated with highly impactful flooding events, are of great scientific interest. However, these events are largely controlled by inherently noisy processes like precipitation and temperature, which has limited the ability to isolate the influence of global warming on flooding trends to date. Here, we apply a method to determine how much each year's most extreme flood event has been influenced by natural variability in the climate system. In doing so, we can evaluate an "adjusted" timeseries of maximum annual floods from 1970 to 2020, which represents changes in flooding due to rising greenhouse gases. We find that increases in flood hazard are likely to occur, as the current phase of natural variability shifts, for basins with lower decreases in their historical annual water availability. These changes will be primarily due to warming‐driven snowpack loss and enhanced heavy rainfall. Lastly, basins with strong drying trends in their annual water availability will likely maintain their historically observed decreasing trends in flood hazard. Key Points: Internal atmospheric‐circulation variability can profoundly influence extreme streamflow trends across the western United States Anthropogenic climate change is driving decreasing trends in flood hazard across basins with strong drying trends in annual streamflow Anthropogenic flood hazard trend is positive in basins with weak drying, intensifying precipitation extremes and/or decreases in snowpack